Study of the labor characteristics in managerial positions of sports organizations in the Community of Madrid: A gender perspective - Gallardo Pérez, Jana; León Quismondo, Jairo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The labor situation of women and men in the sports sector has traditionally been different, affected mainly by factors, such as motherhood or cultural aspects. The aim of this research was to explore the labor situation of women and men who hold managerial positions within sports organizations located in the Community of Madrid (Spain). For this purpose, a sample of 401 participants (200 women and 201 men) from various public and private sports organizations was surveyed. A questionnaire was applied for collecting data on their labor situation and analyzed with the Chi-square test, the Phi coefficient, or the Contingency coefficient (CC). Among the main results, a higher representation of men (55.2%) compared to women (38.5%), as well as a salary gap, was observed in management positions within sports organizations. These data are considered of interest, mainly for the personnel selection departments of the different sport entities, as well as to promote equity policies at any organizational level.